Renuka Ray: A Pioneering Woman in Indian Women’s Movement - Bhadra(Sur Ray), Paramita (International Journal of Psychosocial Rehabilitation, 2020)
Renuka Ray was a pioneering woman in Indian Women’s movement. Belonging to an affluent and educated family in undivided Bengal, she opted for an unconventional life of social service. Inspired by Mahatma Gandhi she left college and donated her jewellery to the cause of non-cooperation movement. She was one of the two women to enter the Legislative Assembly where she voiced her opinion on the reform of Hindu marriage bills and the decision to withdraw the ban on women working in underground mines. Women’s movement in India, she felt, was fundamentally different from the women’s movement in the West in the sense that here the movement was not for the establishment of women’s rights but rather for the restoration of rights which women had enjoyed in the past when Indian civilization was at its height. She observed that women in every sphere were lagging far behind. They were completely under patriarchal control. Even after independence majority of women had limited opportunities with regard to education and employment. Constant child-birth without proper medical facilities had made women prematurely old. She urged society to give economic value to the labour put down by women in domestic front. She was also one of the founder members of the Women Co-ordinating Council under which several women’s organisations came together to work especially during the time of emergencies. She was feminist in the sense that she believed that women should get all the opportunities to develop themselves fully, but she did not believe in creating a division between men and women. Rather, she felt, they were complementary to each other. She also believed that women’s organisations should not confine themselves only with the welfare of women, but should also concentrate on the uplift and welfare of the entire society.